Pengaruh Etika Berbahasa Indonesia Yang Buruk di Media Sosial Terhadap Individu - Gabe Hotmaida Silaban; May Sariah Pangaribuan; Pani Agriani Simanjuntak; M.Surip (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
especially among young people. However, the use of social media can also cause various problems, including the use of unethical language. This research discusses the influence of poor Indonesian language etiquette on social media on individuals. In this research, researchers used descriptive methods to identify language errors that occur on social media, especially on Instagram. The research results show that the use of Indonesian on social media often experiences errors in spelling, diction and grammatical structure. These mistakes can lead to misunderstandings and ineffective use of language. Apart from that, this research also found that the use of Indonesian on social media often experiences variations in Indonesian with English, slang and local regional languages. The conclusion of this research shows that the unethical use of Indonesian on social media can have a negative impact on individuals. Therefore, more awareness and attention is needed in using Indonesian on social media in order to communicate effectively and not cause misunderstandings.